‘Modern gardeners’ with Rustic Ideals: Fruitful Congruencies between John Ruskin and William Robinson - Aurélien Wasilewski (Cahiers Victoriens et Edouardiens)
William Robinson, a gardener and magazine editor, is usually celebrated as the originator of the wild garden and the English flower garden, aesthetic forms that flourished in the second half of the nineteenth century in England. He greatly admired John Ruskin and made his the latter’s ‘definition of the vegetable kingdom [which] is quite different from the definition of botanists generally, but perhaps not on that account less true. ‘Corn for the granary, timber for the builder’s yard, flowers for the bride’s chamber, and moss for the grave’. In a word, food, shelter, and beauty for all of us, living or dead, are the sum total of a world’s vegetation’. This short quote from ‘Ruskin’s garden at Denmark Hill’, published in the December 11 issue of The Garden, 1886, sums up the extent of what William Robinson shared with John Ruskin, from his aesthetic theories to his social commitments, spiritual stance or environmental conscience. In fact, it appears that William Robinson read Ruskin extensively, but rather exclusively from the point of view of the gardener and we would argue that William Robinson considered John Ruskin’s work as an inspirational matrix on which he could base his aesthetic choices, new gardening practices, and even editorial and literary enterprises. In an attempt at mapping the numerous outcrops of Ruskin’s body of work in Robinson’s garden publishing, this paper will endeavour to untangle the ties between the two Victorian gardeners. To what extent were the views of those ‘modern gardeners’ on ‘flora and the vegetable kingdom’ congruent? What stylistic and formal developments did such elective affinities entail in their respective gardens and theories? What ethical considerations underlie such new gardens and practices?